Post-Accession Crisis in the New Member States: Progressing or Backsliding in the EU? - Agh, Attila (Studies of Transition States and Societies, 2010)
The global crisis broke out ‘externally’ when the ‘internal’ institutional crisis in the EU reached its peak. In addition, the new member states were still in the post-accession crisis. These three types of ‘crises’ can be observed: first, a deep systemic crisis is ongoing in the global world; second, the creative crisis is the usual way of development in the EU; and finally third, the serious problems, disturbances, troubles in the new member states are transitory as the unavoidable contradiction of Europeanisation within the EU. Nonetheless, in the deepening-widening relationship, the new members are the main losers of the triple crisis, since the global financial crisis has broken out when they have been in their most vulnerable situation, so it deteriorates significantly their efforts to catch up and reach ‘effective membership’.Two alternative scenarios can be outlined: (1) the ‘post-communist track’ and (2) the ‘completing the membership’ scenario. The first scenario has been based on the ‘Prague-Vladivostok doctrine’, which presupposes that these ‘post-communist countries’ are basically of the same nature from Prague to Vladivostok and due to the burden of history they are doomed to fail in the process of catching up in the EU. The completing the membership scenario has been based on the Europeanisation process, which indicates that the new member states can reach effective membership by 2015. All in all, a new kind of controversial progress has begun, since the global economic and social crisis with new dangers and new opportunities has accelerated the necessary domestic reforms in the new member states.